ACSM's exercise testing and prescription - Bayles, Madeline P.; Swank, Ann Marie (Wolters Kluwer, 2018)
"As an American College of Sports Medicine publication, this book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world. The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book. A full section devoted to special populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they'll see in practice. Comprehensive case studies written by experts to reinforce practical applications of concepts." -- Publisher